Assessing Differences Between Epigenetic versus Chronologic Age for Cardiovascular Risk Assessments in the United States - Ramzi Ibrahim; Balaji Tamarappoo; Kwan Lee; Chadi Ayoub; Khurram Nasir; Reza Arsanjani; Sadeer G. Al-Kindi (Circulation: Population Health and Outcomes, 2026)
Background: Epigenetic clocks derived from DNA methylation estimate biological aging and have been associated with cardiometabolic death. We evaluated whether substituting epigenetic age for chronologic age within PREVENT altered associations with all-cause and cardiovascular mortality or improved discrimination. Methods: We analyzed National Health and Nutrition Examination Survey 1999-2002 data linked to National Death Index follow-up through December 31, 2019. Adults aged 50-79 years without baseline cardiovascular disease and with DNA methylation data were included. PREVENT is a primary-prevention framework incorporating demographic, cardiometabolic, renal, and treatment factors. Exposures were PREVENT estimates calculated using chronologic age or 8 epigenetic ages substituted for chronologic age, with other inputs unchanged. Survey weighted Cox models estimated associations with all-cause and cardiovascular mortality per 5-percentage-point higher predicted risk. Weighted Harrell C statistics assessed discrimination; 95% CIs were obtained by bootstrap resampling. Results: The cohort included 1,516 participants (weighted mean age, 60.3 years; SD, 8.0) with a mean follow-up of 17.35 years; 507 participants died, including 140 cardiovascular deaths. Each 5-percentage-point increase in chronologic PREVENT risk was associated with all-cause mortality (HR, 1.57; 95% CI, 1.45-1.70) and cardiovascular mortality (HR, 1.66; 95% CI, 1.501.84). Biologic variants showed similar associations for all-cause mortality (HR range, 1.391.57) and cardiovascular mortality (HR range, 1.47-1.67). Chronologic PREVENT showed higher discrimination for all-cause mortality (C, 0.74; 95% CI, 0.72-0.77) than biologic variants (C range, 0.66-0.73) and for cardiovascular mortality (C, 0.78; 95% CI, 0.73-0.84) than biologic variants (C range, 0.71-0.77). Conclusions: Biologic PREVENT variants were associated with mortality but did not improve discrimination compared with chronologic PREVENT, suggesting biological aging metrics may complement rather than replace chronological age in cardiovascular risk prediction.